EXPLORING THE POTENTIAL PHARMACOLOGICAL EFFECT OF THYMOQUINONE IN AMELIORATING THE ACQUISITION AND EXPRESSION OF VINCRISTINE INDUCED NEUROPATHIC PAIN IN MICE - Mehreen Arif; Naeem Ur Rehman; Hurmat Malik; Muhammad Usman; Ahmed Tokhi; Syeda Sharmeen Shah; Prof Dr.Khalid Rauf (International Journal of Pharmacy & Integrated Health Sciences)
Background: Chemotherapy-induced neuropathy (CIPN) is the most severe consequence, causing both sensory and motor impairment with an incidence of between 19% and over 85%. Leukaemia, lymphoma, and sarcoma are just a few of the cancers that are treated using vincristine (VCR), a typical anticancer treatment used in chemotherapy. Peripheral neuropathy caused by vincristine is the primary impediment to the efficacy of ongoing anti-cancer treatment and continued use. Objectives: The current study's goal was to contemplate the significance of thymoquinone on the development and expression of vincristine-induced neuropathy. Methodology: All groups except normal saline were administered vincristine 0.1mg/kg i.p for 14 days. In selected groups Gabapentin (75mg/kg) and thymoquinone were administered at 10, 20, and 30 mg/kg/day for 14 days orally along with vincristine (acquisition) and once at day 14 (expression). Thermal hyperalgesia and mechanical allodynia were quantified on days 1, 6, and 14 after 30, 60, 90, and 120 minutes. The data were processed using the Students’t-test and post hoc Dunnett's test. Results: The acquisition and expression of thermal hyperalgesia as well as mechanical allodynia was significantly improved by thymoquinone at all the tested doses at days 6 and 14 as well as after 30, 60, 90, and 120 minutes significant improvement was observed. Conclusion: It is manifested that TQ can be an impending candidate for the management of vincristine-induced neuropathy.